Studies on Schismatoglottideae(Araceae) of Borneo VII : Schottarum and Bakoa, two new genera from Sarawak, Malaysian Borneo - Peter C., Boyce; Sin Yeng, Wong (SpringerOpen Journal, 2008)
Schottarum P. C. Boyce & S. Y. Wong and Bakoa P. C. Boyce & S. Y. Wong are described as new genera from Sarawak, each with one species : Schottarum sarikeense (Bogner & M. Hotta) P. C. Boyce & S. Y. Wong based upon Schismatoglottis sarikeensis (Bogner & M. Hotta) Bogner & A. Hay and Bakoa lucens (Bogner)...